The effect of nitrogen lone-pair interaction on the conduction in a single-molecule junction with amine-Au bonding - Sugita, Yoshihiro (Sci Rep, 2018)
We have applied our previously developed three-dimensional dynamic probe method to analyze the conductance in a Au-/1,4-benzenediamine (BDA)/Au single molecule junction. This structure is a typically used example to demonstrate the high performance of the break junction (BJ) method for measuring conductance with small variations, however, details of the interaction of the nitrogen (N) lone-pair in the amine group with a Au electrode, which is considered to have a fundamental role in determining the conductance of the single molecule junction with the amine, have not yet been clarified and still remain an important issue to be resolved. In this study, we have succeeded, for the first time, in observing the site-dependent change in conductance of this system while the molecular conformation was accurately controlled, and the results were well reproduced by a simulation taking account of the effect of the N lone-pair in an amine bonding with a Au electrode.